Assessment of the surface roughness of a flowable resin subjected to different salivary pH - Amaya-Sanchez, Marjorie Guissela (2021)
Objective: To determine the surface roughness and color stability of a nanohybrid resin subjected to different salivary pH at different times. Materials and methods: experimental, comparative, in vitro study, in which 45 discs of EA2 nanohybrid resin (OPALLIS FGM) of 10 mm in diameter and 1 mm in thickness. They were randomly distributed in three groups (n = 15), each of the resin discs was subjected to an evaluation of its roughness by means of a digital roughness meter (TESTER SRT-6200) and color by colorimeter (Tooth Color Comparator). The discs according to their group were immersed in 18ml of artificial saliva modified with citric acid until obtaining saliva of pH 5, 6 and 7 respectively and placed in specific reservoirs maintained at 37 ° C, according to the specifications of the ANSI / ADA n0 standard. 66, after 168 and 504 hours of storage, a second and third evaluation was carried out. For the statistical analysis, the Friedman and Kruskal Wallis tests were used. Results: The three salivary pHs modified the surface roughness of the material used in a more evident way, pH 5, observing an increase in surface roughness with the time of exposure to substances with different pH analyzed (p <0.01), the color showed an evident increase of 4 tones in all the samples. Conclusions: The increase in roughness was proportional with time and inversely proportional with the pH, more evident with pH5. The color evaluation mechanism did not allow obtaining a conclusive data.